Coordinating heterogeneous IoT devices by means of the centralized vision of the SDN controller - Galán-Jiménez, Jaime; Berrocal, Javier; García-Alonso, José; Canal-Velasco, José Carlos; Murillo, Juan M. (My University, 2017)
The IoT (Internet of Things) has become a reality during recent years. The desire of having everything connected to the Internet results in clearly identified benefits that will impact on socio economic development. However, the exponential growth in the number of IoT devices and their heterogeneity open new challenges that must be carefully studied. Coordination among devices to adapt them to their users' context usually requires high volumes of data to be exchanged with the cloud. In order to reduce unnecessary communications and network overhead, this paper proposes a novel network architecture based on the Software-Defined Networking paradigm that allows IoT devices coordinate and adapt them within the scope of a particular context.
Keywords: Internet; Redes de ordenadores; Internet of Things; Situational-Context; Software-Defined Networking